Correlation Between ERCP Implementation Time and Outcomes of Patients with Acute Cholangitis Due to Choledocholithiasis - Ayundra, Muhammad Hilmy; Rudiman, Reno; Hapsari, Putie (Faculty of Medicine, Universitas Padjadjaran, 2025)
Acute cholangitis is a serious condition, and timely ERCP is essential for effective management. This prospective cohort study was conducted at Dr. Hasan Sadikin Hospital in Bandung, Indonesia, from June 2023 to April 2024, to evaluate the feasibility of performing ERCP beyond 48 hours in the presence of various limitations. The study included patients with acute cholangitis caused by common bile duct stones. The ERCP timing was categorized into three groups: less than 48 hours, 48-72 hours, and more than 72 hours. Outcomes measured were hospital stay duration, ICU admission, and 30-day mortality. Of these patients, 52.8% underwent ERCP at 48-72 hours, 27.8% after 72 hours, and 19.4% before 48 hours. The median hospital stay was 7.5 days (IQR 3-15). ICU admissions occurred only in patients receiving ERCP after 72 hours (30.0%), a significantly higher rate compared to the other groups (p=0.014). A strong correlation was found between delayed ERCP and longer hospital stays (r=0.711, p<0.01), as well as ICU admission (r=0.405, p=0.014), though no significant correlation with mortality was observed (r=-0.021, p=0.905).